Influence of crop based water and nutrient strategies on physiological aspects of apple trees ‘Brookfield Gala’ - Lebese, Thabiso C. (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD(Agric) (Horticulture))--Stellenbosch University, 2008.